ARI updates 2012: moving beyond numbers / Accounting Research Institute (Accounting Research Institute (ARI), 2012)
Since its inception in 2002, ARt has atways wanted to mark Its presence on the world map. Hence, its recognition as a Higher Institutions' Centre of Excellence (HICoE) in 2010 constitutes the right platform and avenue for ARI to fulfil its dream. The niche research area in Islamic Financial Criminology (IFC) creates a unique and strategic opportunity for ARI to support Malaysia's vision of becoming a global Islamic Finance hub. In essence, research in IFC focuses on two strategic thrusts: (i) developing new products, models or policies for the Islamic Finance sector and (ii) enriching knowledge and competency in financial criminology to mitigate financial fraud from infiltrating the sector.